C-Doped LiVO3 Honeycombs Derived from the Biomass Template Strategy for Superior Lithium Storage - Shi, Jiayue (Langmuir : the ACS journal of surfaces and colloids, 2023)
LiVO3 as a prospective anode for lithium-ion batteries has drawn considerable focus based on its superior ion transfer capability and relatively elevated specific capacity. Nevertheless, the inherent low electrical conductivity and sluggish reaction kinetics hindered its commercial application. Herein, C-doped LiVO3 honeycombs (C-doped LiVO3 HCs) are designed via introducing low-cost and scalable biomass carbon as a template, and the influence of the structure on the lithium storage property is systematically studied. The prepared C-doped LiVO3 HC electrode delivers a high reversible capacity of 743.7 mA h g-1 at 0.5 A g-1 after 400 cycles and superior high-rate performance with an average discharge capacity of 420.8 mA h g-1 even at 5.0 A g-1. The remarkable comprehensive electrochemical performance is attributed to the high electrical conductivity caused by carbon doping and rapid ion transport triggered by the honeycomb structure. This work may offer a rational design on both the hierarchical structure and doping engineering of future battery electrodes